2014
DOI: 10.1002/nme.4788
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of three-dimensional analysis of regularized singularities

Abstract: SUMMARYIn computational mechanics, the quadrature of discontinuous and singular functions is often required. To avoid specialized quadrature procedures, discontinuous and singular fields can be regularized. However, regularization changes the algebraic structure of the solving equations, and this can lead to high errors. We show how to acquire accurate and consistent results when regularization is carried out. A three-dimensional analysis of a tensile butt joint is performed through a regularized extended fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The support of δ ρ noncompact, and it is necessary to introduce a truncation length beyond which the value of δ ρ is not to be evaluated. We found [19] that a truncated support length of 40ρ provides a satisfying compromise between computational burden and accuracy, at least for the present H ρ . In the following developments, the lengths ℓ ρ,M and ℓ ρ,m will denote the width of the truncated supports of δ ρ for ρ = ρ M and ρ = ρ m , respectively.…”
Section: Width Of the Regularized Damage Bandmentioning
confidence: 75%
“…The support of δ ρ noncompact, and it is necessary to introduce a truncation length beyond which the value of δ ρ is not to be evaluated. We found [19] that a truncated support length of 40ρ provides a satisfying compromise between computational burden and accuracy, at least for the present H ρ . In the following developments, the lengths ℓ ρ,M and ℓ ρ,m will denote the width of the truncated supports of δ ρ for ρ = ρ M and ρ = ρ m , respectively.…”
Section: Width Of the Regularized Damage Bandmentioning
confidence: 75%
“…(54), δ ρ,M is computed in terms of ρ M , so that the interaction radius equals ρ,M /2, corresponding to averaging over a volume of width 40ρ M . We have heuristically verified that ρ M provides a satisfying compromise between computational burden and accuracy [20]. Remarkably, both the local stress ( 53) and the nonlocal stress ( 54) are computable in any element whether enriched or not, and this is useful when the element under consideration has not yet been enriched.…”
Section: Direction-tracking Strategymentioning
confidence: 88%
“…where Being the support of δ ρ noncompact, it is necessary to introduce a truncation length beyond which δ ρ is not evaluated. The approximation issues related to the choice of the truncation length were investigated in [20]. In particular, it was found that a truncated support length of 40ρ provides a satisfying compromise between computational burden and accuracy, at least for the present H ρ .…”
Section: Width Of the Regularized Damage Bandmentioning
confidence: 99%
See 1 more Smart Citation
“…Their approach to constructing polynomial regularizations using the Chebyshev basis has a similar flavor to our approach, as will be seen in Section 3. In a different approach, Benvenuti et al [5] study the case of regularizations that are not compactly supported but have rapidly decaying Fourier transforms in the context of extended finite element methods (XFEM) [4]. The authors demonstrate that such regularizations lead to lower numerical errors since they can be integrated using common quadrature methods such as Gauss quadrature.…”
Section: Introductionmentioning
confidence: 99%